Pan-tibial avascular necrosis in a 12-year-old boy: a case report. Issue 1 (January 2018) - Gopinathan, Nirmal R.; Saibaba, Balaji; Santhanam, Siva S.; Syam, Kevin
Abstract : We report a unique case of post-traumatic avascular necrosis of tibia in a 12-year-old boy following a Salter–Harris type II physeal injury of the proximal tibia. The diagnosis was made on the basis of classical radiological findings. The only clinical symptom was diffuse shin pain. The patient was managed conservatively. At our 2-year follow-up, there was clinical and radiological evidence of spontaneous resolution of avascular necrosis, but with sequelae. The child developed a limb-length discrepancy and genu valgum. The parents of the child refused further treatment.